PEGylation enables the specific tumor accumulation of a peptide identified by phage display - Mier, Walter; Krämer, Susanne; Zitzmann, Sabine; Altmann, Annette; Leotta, Karin; Schierbaum, Ursula; Schnölzer, Martina; Eisenhut, Michael; Haberkorn, Uwe (Organic & biomolecular chemistry, 2013)
Peptides are excellent alternatives to small molecules and proteinaceous drugs. Their high medicinal potential for diagnostic and therapeutic applications has prompted the development of tumor targeting peptides. Despite its excellent tumor binding capacity, FROP-DOTA (H-Glu-Asn-Tyr-Glu-Leu-Met-Asp-Leu-Leu-Ala-Tyr-Leu-Lys(DOTA)-NH2), a peptide that we had identified in phage display libraries, revealed slow binding kinetics. Consequently, biodistribution studies showed that its excretion forestalled a significant tumor accumulation. The aim of this study was to investigate whether the conjugation of PEG to FROP-DOTA resulted in a derivative with a prolonged residence time in the blood. A synthetic method for the PEGylation of the tumor specific peptide FROP-DOTA was developed. Thereafter, binding studies were done in vitro and a biodistribution was performed in tumor bearing animals. These were compared to the data obtained with FROP-DOTA. The binding kinetics of the PEGylated FROP-DOTA was even slower than that of FROP-DOTA. Biodistribution studies of the labeled conjugate in mice bearing human FRO82-2 tumors showed a time dependent increased uptake of the PEGylated peptide with a high retention (at 24 h p.i. 76% of the maximal activity concentration persisted in the tumor). The highest uptake values were determined at 120 min p.i. reaching 2.3%ID/g tumor as compared to 0.06%ID/g observed for the non-PEGylated derivative at 135 min p.i. Apparently, PEGylation provides a substantially improved stabilization in the circulation which allowed a stable tumor accumulation.
Gesehen am 21.05.2021